Radiopacity evaluation of contemporary luting cements by digitization of images - Reis, José Maurício dos Santos Nunes [UNESP]; Jorge, Érica Gouveia [UNESP]; Ribeiro, João Gustavo Rabelo; Pinelli, Ligia Antunes Pereira [UNESP]; Abi-Rached, Filipe de Oliveira [UNESP]; Tanomaru Filho, Mário [UNESP] (Hindawi, 2012)
The aim of this study was to evaluate the radiopacity of two conventional cements (Zinc Cement and Ketac Cem Easymix), one resin-modified glass ionomer cement (RelyX Luting 2) and six resin cements (Multilink, Bistite II DC, RelyX ARC, Fill Magic Dual Cement, Enforce and Panavia F) by digitization of images. Methods. Five disc-shaped specimens (10×1.0 mm) were made for each material, according to ISO 4049. After setting of the cements, radiographs were made using occlusal films and a graduated aluminum stepwedge varying from 1.0 to 16 mm in thickness. The radiographs were digitized, and the radiopacity of the cements was compared with the aluminum stepwedge using the software VIXWIN-2000. Data (mmAl) were submitted to one-way ANOVA and Tukey's test (=0.05). Results. The Zinc Cement was the most radiopaque material tested (<0.05). The resin cements presented higher radiopacity (<0.05) than the conventional (Ketac Cem Easymix) or resin-modified glass ionomer (RelyX Luting 2) cements, except for the Fill Magic Dual Cement and Enforce. The Multilink presented the highest radiopacity (<0.05) among the resin cements. Conclusion. The glass ionomer-based cements (Ketac Cem Easymix and RelyX Luting 2) and the resin cements (Fill Magic Dual Cement and Enforce) showed lower radiopacity values than the minimum recommended by the ISO standard.
Keywords: Radiopacidade; Cimento odontológico